The subacute behavior of arterial blood pressure in street runners after a session of high-intensity continuous and interval training: Study protocol - Atilio Cabassa Junior, Moises; Martins Cunha, Raphael (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Street running is a form of exercise, often pursued recreationally, that has been growing in popularity in recent years. Among the training methods, both moderate-intensity continuous running and high-intensity interval running have been prescribed. However, while the latter is motivating, it requires further investigation regarding cardiovascular responses. Objectives: Evaluate the subacute blood pressure responses in healthy young adults, who are street runners, after a session of high-intensity interval running and a session of moderate-intensity continuous running. Methods: This is a cross-sectional study with 10 street-runners, who underwent 3 protocols continuous aerobic (CA); high-intensity interval (HII); and control (C). In CA group, a 3000m continuous running session was performed at 75% of the heart rate reserve. In HII group, a similar volume session was conducted, consisting of 7 cycles of stimulus and recovery, where 300m will be run at maximum speed followed by 100m of passive recovery with walking. And in C group, no exercise was performed. Blood pressure measurements will be taken before, immediately after, and every 10 minutes up to 40 minutes after the end of the protocols. Considerations: This study protocol aims to provide additional contributions to the understanding of the subacute hemodynamic responses associated with high-intensity interval running and moderate-intensity running.